Purification and Identification of Antioxidant Peptides from Enzymatic Hydrolysates of Tilapia (Oreochromis niloticus) Frame Protein - Fan, Jian; He, Jintang; Zhuang, Yongliang; Sun, Liping (Molecules (Basel, Switzerland), 2012)
Tilapia frame protein was hydrolyzed by different proteases, including properase E, pepsin, trypsin, flavourzyme, neutrase, gc106 and papain, to obtain antioxidant peptides. The tilapia frame protein hydrolysate (TFPH) obtained by trypsin exhibited the highest degree of hydrolysis and antioxidant activity. Three series of peptides (TFPH1, TFPH 2 and TFPH 3) were obtained by ultrafiltration of TFPH through molecular weight cut-off membranes of 5, 3 and 1 kDa, respectively, and their IC50 values on scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, superoxide anion radical (•O2), hydrogen peroxides (H2O2) and hydroxyl radical (•OH) activities were determined and compared with glutathione (GSH). The results showed that TFPH1 had the highest antioxidant activity. TFPH1 was further purified using ion exchange chromatography, gel filtration chromatography, and reversed phase high performance liquid chromatography (RP-HPLC). Finally, two antioxidant peptides were identified and the amino acid sequences were identified as Asp-Cys-Gly-Tyr (456.12 Da) and Asn-Tyr-Asp-Glu-Tyr (702.26 Da), respectively. The IC50 values of two peptides on hydroxyl radical scavenging activity were 27.6 and 38.4 μg/mL, respectively.